"Seeing a Brighter Future" – Experiences of Adolescents with Common Mental Disorders Receiving the Problem-Solving Therapy "Youth Friendship Bench" in Zimbabwe. (2nd November 2021) - Broström, Sander; Johansson, Björn Axel; Verhey, Ruth; Landgren, Kajsa
Abstract: In Zimbabwe common mental disorders are prevalent among adolescents and the treatment gap is large. The recently introduced Youth Friendship Bench intervention (YouFB) addresses this gap by task-shifting youth lay health workers to offer a culturally contextualised, manual-based, six-session problem-solving therapy to adolescents, 16-19 years of age. The aim of this study was to explore participants´ experiences of YouFB to attain a first insight into this novel intervention. Interviews with nine adolescents were analysed using qualitative content analysis on a latent level. The experience of YouFB was positive, perceived to offer hope and relief from feelings of isolation and uncertainty, increase manageability of problems, and contribute to feelings of autonomy, resulting in a feeling of optimism about the future. The notion among participants that this brief intervention had such a positive influence on their lives, sparks interest because of its applicability in low-resource settings.